Advanced cutaneous squamous cell carcinoma: A retrospective analysis of patient profiles and treatment patterns—Results of a non-interventional study of the DeCOG. (June 2018) - Hillen, Uwe; Leiter, Ulrike; Haase, Sylvie; Kaufmann, Roland; Becker, Jürgen; Gutzmer, Ralf; Terheyden, Patrick; Krause-Bergmann, Albrecht; Schulze, Hans-Joachim; Hassel, Jessica; Lahner, Nina; Wollina, Uwe; et al.
Abstract: Background: Advanced cutaneous squamous cell carcinoma (aSCC) is an area of unmet medical need and no treatment standards are established. Recently, an anti-PD-1 inhibitor received FDA breakthrough therapy designation. The aim of the study was to describe the clinical course, therapeutic management and prognosis of aSCC under real-life conditions. Patients and methods: In a retrospective study performed in 24 German and Austrian hospitals and doctor's offices, patient and tumour characteristics of patients diagnosed with aSCC between January 1, 2010 and December 31, 2011 and their disease course was documented. Advanced SCC comprised either locally advanced SCCs (laSCC) or metastatic SCCs (mSCC) with any kind of metastatic spread. Results: Data of 190 patients with aSCC were analysed. Median age at time of diagnosis of aSCC was 78 years. LaSCC was diagnosed in 76 patients (40%), 114 patients (60%) had mSCC. Once diagnosed with laSCC, most patients (59%) did not receive any therapy, whereas in 92% of mSCC patients at least one type of therapy was performed. Only 32 patients (29 mSCC, 3 laSCC) received systemic antitumour therapies, mostly EGFR inhibitor-based regimens. Mean duration of response was short (17-months laSCC patients, 3-months mSCC patients). Only 2 patients achieved a complete response, 27% had a partial response, 43% disease stabilisation. At diagnosis of aSCC, ECOG status was 0–1 in most patients. Non-malignant comorbidities influenced the decision on SCC-specific therapy in 39 patients (21%). Conclusions: Our data show the high medical need for efficient and tolerable antitumour therapies and demonstrate that despite older age and comorbidities, most patients can be expected to be fit for treatment. This study provides a historical context for emerging aSCC treatments. Highlights: Advanced cutaneous squamous cell carcinoma (aSCC) is a highly aggressive but poorly characterised disease. Real-life data of 190 patients describe patient characteristics and disease course. Only few patients with locally advanced SCC receive treatment. In metastatic SCC, EGFR inhibitors were mostly used with short treatment response. Despite older age and comorbidities, patients can be expected to be fit for treatment.